Training in The Use of Social Media to Enable Residents to Take Up Entrepreneurial Opportunities in Sub-District RT 01/RW 08, Tegal Gundil, Bogor City: Pengabdian - Fujiyati; Lilis Cucu Sumartini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Information technology is currently developing very rapidly. These developments affect the way we live and the way we carry out our daily activities. With the ever-increasing use of the Internet, people can easily and quickly access almost any information they need. Many people use various social media platforms to interact and communicate with others for business purposes, to share daily activities and to socialise with each other online. In addition to being a communication tool, social media also has a business function. This training was conducted to provide the training participants with the insight that opportunities for entrepreneurship can be discovered using social media, especially Instagram and WhatsApp, if these social media platforms are used extensively and actively in the daily lives of the participants. The training was conducted using the lecture method with participants from RT 01/RW 08 Kelurahan Tegal Gundil Kecamatan Bogor Utara Kota Bogor. The training aimed to create new awareness so that the participants would be able to apply the training materials in their daily lives.